2010
DOI: 10.1097/sla.0b013e3181e985a1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Body Mass Index on Groin Hernia Surgery

Abstract: In this large and unselected population of patients with a first surgical procedure for groin hernia a relative dominance of female and femoral hernias presented as an emergency condition was observed in the low BMI group. The prevalence of obesity was markedly low. Both lean and obese patients had an increased risk for postoperative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
1
9

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 19 publications
4
63
1
9
Order By: Relevance
“…The patients included in this study were not found to exhibit any statistically significant differences in terms of sex, age, comorbidities, ASA scores or body mass indices when compared to the general population [25,26]. The majority of patients was male, of normal weight and demonstrated ASA scores of either I or II.…”
Section: Discussionmentioning
confidence: 99%
“…The patients included in this study were not found to exhibit any statistically significant differences in terms of sex, age, comorbidities, ASA scores or body mass indices when compared to the general population [25,26]. The majority of patients was male, of normal weight and demonstrated ASA scores of either I or II.…”
Section: Discussionmentioning
confidence: 99%
“…al. 2007;Rosemar, et. al., 2010) en el estudio predominó el grupo de obreros y campesinos, aunque no demostraron riesgo significativo de recurrencia (p>0.05).…”
Section: Discussionunclassified
“…La tasa de recurrencias aumenta con el número de intentos previos a causa de pérdida de tejidos, friabilidad y retracción cicatrizal; (Flum, Horvath & Koepsell, 2003;Bisgaard, Bay-Nielsen, Christensen, & Kehlet, 2007) evidentemente la primera reparación tendrá mayor posibilidad de éxito, y la recidiva es frecuente tras cualquier reparación secundaria de una hernia recurrente. Los factores desencadenantes han sido muy bien estudiados, y uno de los principales es la hiperpresión intraabdominal, originada por tos crónica, prostatismo y estreñimiento; (Lau, Fang, Yuen & Patil, 2007;Jansen, Klinge, Jansen, & Junge, 2009;Rosemar, Angerås, Rosengren, & Nordin, 2010), otros factores asociados constituye un defecto del metabolismo de colágena, debilidad muscular y tensión de la línea de sutura. (Arregui, & Young, 2005).…”
Section: Introduccionunclassified
“…This is in line with observations from Rosemer et al who could demonstrate a similar U-shaped correlation between BMI and postoperative complication, with higher risks for BMI < 20 as well as for BMI > 25. A BMI, which is too high, obviously is as bad as when it is too low [20]. Ignorance of this U-shaped relation will likely end up in non-significant results, when comparing means or testing 2 × 2 tables with Chi [2].…”
Section: Limitation 5: Mode Of Interference Often Is Not Defined For mentioning
confidence: 99%